55.6k views
1 vote
Help me, I need a step by step solution ASAP

Help me, I need a step by step solution ASAP-example-1
User Dimpiax
by
5.2k points

1 Answer

2 votes

Answer:

a)


x=-1\\x=-(3)/(4)

b)


x=(11)/(6)

Explanation:


Formula: x=\frac{-b\frac{+}{}√(b^2-4ac) }{2a}


a)-4x^2+7x-3=0

a= -4

b= 7

c= -3


x=\frac{-(7)\frac{+}{}√((7)^2-4(-4)(-3)) }{2(-4)}


x=\frac{-7\frac{+}{}√(49-48) }{-8}


x=\frac{-7\frac{+}{}√(1) }{-8}


x=\frac{7\frac{+}{}1 }{-8}

------------------------------


x=(7+1 )/(-8)=(8)/(-8)=-1

or


x=(7-1 )/(-8)=(6)/(-8)=-(3)/(4)

------------------------------


b)36x^2-132x+121=0

a= 36

b= -132

c= 121


x=\frac{-b\frac{+}{}√(b^2-4ac) }{2a}


x=\frac{-(-132)\frac{+}{}√((-132)^2-4(36)(121)) }{2(36)}


x=\frac{132\frac{+}{}√(17424-17424) }{72}


x=\frac{132\frac{+}{}√(0) }{72}


x=\frac{132\frac{+}{}0 }{72}

------------------------------------------------


x=(132)/(72)


x=(132/6)/(72/6)=(22)/(12)=(11)/(6)

User John Siniger
by
6.0k points